Numerical Modeling of Sandy Subgrade Reinforcement by Deep Soil Mixing from Ceramic Industries Wastewater Additive - Firouzabadi, Hamed Heidari; Khabiri, Mohammad Mehdi; Bafghi, Kazem Barkhordari (International Journal of Sustainable Construction Engineering and Technology, 2021)
Todays, development of road transportation and settlement of roads on different subgrade are problems of pavement industry. Desert and beach sands in different parts of the world are the results of load bearing, instability and failure against shear stresses. In other points of view, industries produce different wastewaters whose entrance to the natural environment results in environmental problems. This study utilizes numerical models to improve roadbeds made in sandy areas using ceramic industries wastewater. The goal is to investigate the application of experiment results of mixing ceramic industries wastewater, cement and dune sands in different geometrical models of reinforcing weak subgrade. The analysis of pavement reaction has been modeled in software. Using modeling of refined sand as subgrade or pavement layers stabilizer, surface layer settlement was calculated. The maximum settlement calculated from the modeling was compared with international standards.